Dementia and Imagination: a mixed-methods protocol for arts and science research - Vanessa Burholt (BMJ Open, 2016)
Introduction Dementia and Imagination is a multi-disciplinary research collaboration bringing together arts and science to address current evidence limitations around the benefits of art activities in dementia care. It is a large programme of work with a novel combination of methods from health and social sciences together with the arts and humanities to address a key societal challenge – supporting the quality of life of the growing number of people living with dementia. This is examined through the following questions; can art improve quality of life and well-being? If it does make a difference, how does it do this - and why? Does it have wider social and community benefits? Methods and analysis Participants are recruited from residential care homes, NHS wards and communities in three locations in England and Wales. A visual arts intervention is developed and delivered as 1 x 2 hour weekly group session for 3 months to N=100 people living with dementia. Quantitative and qualitative data are collected at three time-points to examine the impact on the quality of life of people living with dementia together with the cost-benefit, and the perceptions of those who care for them (N=100 family and professional carers). Repeated-measures systematic observation of wellbeing is applied during the intervention delivery (intervention versus control condition). Qualitative data is collected from a sub-sample at three time-points (N=35 carers/staff and N=35 people living with dementia) to explore changes in social connectedness. Self-reported outcomes during the intervention delivery are obtained (N=100). Focus groups with intervention participants (N=40) explore perceptions of impact. Social network analysis of quantitative and qualitative data from arts and healthcare professionals (N=100) examine changes in perceptions and practice. Ethics and dissemination The study is approved by North Wales research ethics committee – West. The research findings will be shared through a range of activities. International and national academic conferences and events will be attended to present papers and lead symposia. The project has developed an extensive public engagement and communication strategy. Public engagement projects will target a broad range of stakeholders. There is a regularly maintained project website, which is a resource bank for stakeholders and a continuing legacy from the project. A quarterly newsletter is produced. Policy and practice summaries will be developed from the findings. The visual arts intervention protocol will be developed as a practitioners guide and freely available.Strengths and limitations of this study•Dementia and Imagination is the largest arts and dementia research study in the UK.•The development and delivery of the research involves partnerships between universities, community arts organisations, galleries, the NHS and charities.•It combines methods from health and social sciences together with the arts and humanities to address a key societal challenge – supporting the quality of life of the growing number of people living with dementia.•A limitation is that the study design cannot focus on a more robust test of effectiveness, as this was beyond the remit of the funders